2019
DOI: 10.1051/0004-6361/201936014
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the detectability of water ice in debris disks

Abstract: Context. Water ice is important for the evolution and preservation of life. Identifying the distribution of water ice in debris disks is therefore of great interest in the field of astrobiology. Furthermore, icy dust grains are expected to play important roles throughout the entire planet formation process. However, currently available observations only allow deriving weak conclusions about the existence of water ice in debris disks. Aims. We investigate whether it is feasible to detect water ice in typical de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…The results shown in Figure 6 are qualitatively consistent with those of Kim et al (2019). In addition, the results obtained by Kim et al (2019) show characteristics of the polarization feature in the reflection regime. The discussion presented in Section 3 may provide a physical explanation for these previous results (e.g., Figure 14).…”
Section: Debris Diskssupporting
confidence: 85%
See 3 more Smart Citations
“…The results shown in Figure 6 are qualitatively consistent with those of Kim et al (2019). In addition, the results obtained by Kim et al (2019) show characteristics of the polarization feature in the reflection regime. The discussion presented in Section 3 may provide a physical explanation for these previous results (e.g., Figure 14).…”
Section: Debris Diskssupporting
confidence: 85%
“…To our knowledge, a distinct water-ice feature has not yet been detected in debris disks (see also Hughes et al 2018), although Chen et al (2008) reported a broad peak at 60 − 75 µm that may be due to crystalline water ice. Future space missions, such as JWST, and ground-based facilities, such as E-ELT and TMT, will advance our understanding of water ice in debris disks (Kim et al 2019).…”
Section: Debris Disksmentioning
confidence: 99%
See 2 more Smart Citations
“…The volatile content of the planetesimals is harder to probe through spectral features, though there are mid-and far-IR features due to ice that could be detected by JWST and Spica [45]. However, ALMA is providing a growing body of observations of gas in debris disks which is thought to have a secondary origin, i.e., to have been released from volatile-rich planetesimals, rather than being a remnant of the protoplanetary disk [21,61,60].…”
Section: Planetesimal Compositionmentioning
confidence: 99%